An Appraisal Look into Iraqi EFL Students' L2 Motivational Self-System and It's Correlation with Their Reading Ability : Tinjauan Penilaian L2 Motivational Self-System Mahasiswa EFL Irak dan Korelasinya dengan Kemampuan Membaca Mereka - Kadhim, Ahmed Abed Ali; Kaddam, Methaq Kadhim (Journal of Literature and Education, 2025)
The aim of this study was to examine the relationship between the Iraqi EFL L2 motivating self-system, reading ability, and gender. In order to find answers to the research questions, a correlational methodology was used, and the study was designed as a qualitative investigation. One hundred EFL students from secondary schools in Karbala, Iraq, participated. The present research is remarkable since it integrates the L2 motivational self-system, which takes into account the various viewpoints of the learners of English as a foreign language in a time of globalization. The findings showed that the L2 motivating self-system and reading ability skill were positively correlated, and it also demonstrated that the ought-to L2 self, L2 learning experience, and ideal L2 self were positively and strongly predicted by reading ability. Furthermore, the ought-to L2 self was the most powerful positive predictor of reading ability skill among the three measures of the L2 motivational self-system. Additionally, the results showed that there is not a significant distinction between male and female students' L2 motivating self-systems for learning English. Regarding reading ability skill, there was not any significant difference among the genders of the participants.